Precise control of coordination polymerization via the modification of methylaluminoxane (MAO) - Tanaka, Ryo (Polymer journal, 2020)
Methylaluminoxane (MAO) is known as a versatile activator of transition metal catalysts for coordination polymerization reactions, even though its precise structure and the origin of its activation properties have not been fully investigated. Considering that MAO exists as a counter anion that can interact with cationic metal species in a polymerization medium, the ability to impart structural modifications to MAO would provide a new direction for controlling the polymerization behavior. Here, the modification, the composition control, and a new preparation method of MAO will be summarized, as well as the application of modified MAO for the synthesis of stereoblock polydienes.Methylaluminoxane (MAO) activates various transition metal catalysts for coordination polymerization reactions and exists as a counter anion that can interact with cationic metal species in a polymerization medium. The structural modifications to MAO would therefore provide a new direction for controlling the polymerization behavior. In this review, our recent work about the modification, the composition control, and a new preparation method of MAO is summarized. The application of modified MAO for the synthesis of stereoblock polydienes is also described.